Promoting Export-Led Economic Growth in Nigeria –The Export Processing Zone Option (2016)
The volatility in crude oil production in Nigeria, which in recent times, have been heightened by militant attacks on critical oil installations in the Niger Delta area and the continued price spiral in international oil market has once again brought to the front burner anxieties about the future of the oil sector in the Nigerian economy. The unfolding scenario has again exposed the Nigerian economy to downside risks of volatility in oil prices with attendant Mconsequences and multiple effects on the economy and businesses as well. Since the third quarter of 2015, fallen prices of crude oil and fluctuations in crude oil production in Nigeria have conspired to put the country’s economy in dire straits. The oil price has fallen by more than 50 percent since June 2014, when it was $115 a barrel. It is now consistently below $50 and has been as low as $37. These developments have put the nation’s fiscal operations in quandary. The government has rightly responded by putting in place various fiscal and monetary measures to stem the tide. The federal government has adopted some austere measures to cushion the effect of the persistent drop in revenue. However, the implementation of these short-term measures to shore up revenue could be impeded by political exigencies which often times overrides economic rationality. Thus, a more comprehensive and alternative approach that will promote non-oil export will be a better option. To this end, the authors recommend the revitalization and retooling of the Export Processing Zone (EPZ) Scheme in order to effectively diversify the economy away from oil to an export-led economy.